(untitled) (International journal of artificial intelligence, 2026)
This article examines the paradigm shift in contemporary education driven by innovative approaches. As traditional methodologies fail to meet modern demands, educational institutions must pivot toward active, technology-enhanced, and learner-centric frameworks. This study analyzes key innovations, including Artificial Intelligence integration, gamification, project-based learning, and the flipped classroom model. By evaluating current empirical data and pedagogical theories, the paper provides a comprehensive blueprint for modern educators to foster critical thinking, collaboration, and lifelong learning skills.